1998
DOI: 10.1191/026921598675167321
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a nurse-led multidisciplinary neurological rehabilitation programme using the Nottingham Health Profile

Abstract: These results suggest that the multidisciplinary inpatient approach in neurological rehabilitation has identifiable short-term benefits for the majority of patients. A randomized trial with longer follow-up is required to confirm this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The synthesis started in stage 3 with the transformation of materials from a disparate collection of papers into a format to allow collective analysis according to the assessment schedule. (2000) Does not consider the MS nurse Bennett (1995) Does not consider the MS nurse Burks (1998) Does not consider the MS nurse Campion and Cole (1997) Overview of MS disease not role DiIorio and Price (2001) Educational evaluation not role of ms nurse Davies (1979) Does not consider the MS nurse Gulick and Bugg (1992) Does not consider the MS nurse Halper and Holland (1998a) Overview of MS disease and treatment Forbes and Rafson (1990) Does not consider the MS nurse Koch and Kralik (2001) Does not consider the MS nurse Marks and Millard (1990) Considers standardized instruments in assessment Miller (1993) Does not consider the MS nurse Mills et al (1999) Does not consider the MS nurse Nolan et al (2001) Does not consider the MS nurse Newland (1999) Does not consider the MS nurse Porter and Scullion (2001) Short editorial Schwartz et al (1998) Does not consider the MS nurse Sitzia et al (1998) Deals with inpatient rehabilitation Integrative literature reviews and meta-analyses MS nurse specialists…”
Section: Stage 4 Synthesizing the Evidencementioning
confidence: 99%
“…The synthesis started in stage 3 with the transformation of materials from a disparate collection of papers into a format to allow collective analysis according to the assessment schedule. (2000) Does not consider the MS nurse Bennett (1995) Does not consider the MS nurse Burks (1998) Does not consider the MS nurse Campion and Cole (1997) Overview of MS disease not role DiIorio and Price (2001) Educational evaluation not role of ms nurse Davies (1979) Does not consider the MS nurse Gulick and Bugg (1992) Does not consider the MS nurse Halper and Holland (1998a) Overview of MS disease and treatment Forbes and Rafson (1990) Does not consider the MS nurse Koch and Kralik (2001) Does not consider the MS nurse Marks and Millard (1990) Considers standardized instruments in assessment Miller (1993) Does not consider the MS nurse Mills et al (1999) Does not consider the MS nurse Nolan et al (2001) Does not consider the MS nurse Newland (1999) Does not consider the MS nurse Porter and Scullion (2001) Short editorial Schwartz et al (1998) Does not consider the MS nurse Sitzia et al (1998) Deals with inpatient rehabilitation Integrative literature reviews and meta-analyses MS nurse specialists…”
Section: Stage 4 Synthesizing the Evidencementioning
confidence: 99%
“…23 A number of studies recommend that health professionals should develop specialist skills to respond to the long term interdisciplinary care needs for this population. 24,27,28 Although some initial work has been undertaken to identify caregiver distress in the PD population, little systematic work has been undertaken to examine the care needs of patients with PD and their family caregivers. The question 'who should look after people with PD?'…”
Section: Introductionmentioning
confidence: 99%
“…Using the Nottingham Health Profile (a measure of health-related quality of life), Sitzia et al found improvements in 'pain', 'emotional reactions' and 'physical mobility' and in overall quality of life. 16 A programme consisting of a combination of physiotherapy, occupational therapy and speech therapy for a total of three hours per day for five to seven days per week led to significant improvements in timed up and go, two-minute walk test and finger tapping. 17 Randomised controlled trials (RCTs) have showed mixed results.…”
Section: Effectiveness Of Multidisciplinary Carementioning
confidence: 99%